Development of an attitude assessment instrument pertaining to the thematic learning of second grade elementary students - Lia Santika; Pargito Pargito; Alben Ambarita; Rochmiyati Rochmiyati (Lighthouse Publishing, 2022)
This study aimed to develop an instrument for assessing politeness in the thematic learning of students in elementary schools. The type of research and development used refers to the R&D theory of Borg and Gall. This study included three schools in the Melati cluster, Banjit district. The sample of this study were second grade students of State Elementary School 01 Bonglai. Data collection techniques used were non-test in the form of questionnaires, interviews and documentation. Data analysis used qualitative analysis with descriptive percentage for expert & practitioner validation, and quantitative analysis with Rasch program for validity and reliability. The results of this study indicated that the instrument for assessing politeness in thematic learning in elementary schools that was developed was theoretically and practically feasible.